Identifying the spatiotemporal evolution of nucleic acid testing sites and their influencing factors to support public health emergency management: A case study in Hangzhou, China - Song Yao; Mingjun Cheng; Yunchen Zhu; Xiangyang Quan; Fangqi Wang; Zhaoxuan Xia; Shan Huang; Yonghua Li (Discover Public Health, 2025)
Abstract The Coronavirus Disease 2019 pandemic is a significant global public health emergency. Large-scale nucleic acid testing (NAT) is one of the key measures to control the spread of the virus, yet the geographic aspects of these testing facilities remain underexplored. The strategic location of these NAT sites significantly influences the effectiveness of emergency resource distribution. Identifying the spatiotemporal distribution characteristics and influencing factors of these sites is crucial for enhancing the governance capabilities in urban public health emergencies. We leveraged Python to obtain NAT site data, utilized geographic information systems to analyze the spatiotemporal dynamics of these sites, and employed the optimal primal geographical decomposition (OPGD) model and geographically weighted regression (GWR) model to identify their influencing factors. The results show that: (1) The number of NAT sites underwent four phases over time and exhibited substantial spatial concentration in Shangcheng, Gongshu, Xihu, and Binjiang districts. (2) The population density, human footprint, and the digital elevation model were the dominant potential influencing factors for the location of NAT sites, with the explanatory power of interactions among influencing factors being higher than that of individual factors. (3) The location of NAT sites in the Shangcheng, Gongshu, Xihu, and Binjiang districts has a significant positive correlation with population density, while the relationship was not significant in other regions. These findings can provide decision-making insights for managing public health emergencies in Hangzhou, as well as in other cities with similar economic and policy conditions.